The Value Relevance of Accounting Information: Profitability and Non-Public Ownership In Investment Decision Making - Maya Ari Rosita; Pujiono (Global Financial Accounting Journal, 2024)
Purpose – The purpose of this research to evaluate the relevance of accounting information, particularly Earnings per Share (EPS), Return on Assets (ROA), and Non-Public Ownership (NPO), in investment decision-making. The relevance of accounting information is observed when the information presented in financial statements can influence stock prices and therefore affect user decision-making. Research Method – The research method used is quantitative method with a sample of 59 manufacturing companies from the basic and chemical industry sector. Data analysis was conducted using multiple linear regression techniques to measure the impact of these variables on stock prices. Findings – The results of the study indicate that EPS and ROA have a significant influence on investment decisions, while Non-Public Ownership does not provide significant contributions. Implication – The implications of these findings underscore the importance of considering fundamental factors such as EPS and ROA in the investment decision-making process, while also taking into account the risks associated with Non-Public Ownership that can affect the relevance of financial statements. Keywords: Earnings Per Share (EPS), Investment Decisions, Non-Public Ownership, Relevance of Accounting Information, Return on Assets (ROA)